Occupational Hazards for Healthcare Workers in Hospitals - Cordeiro, Telma (2017)
Book description by publisher: Despite several improvements in risk assessment and exposure prevention, the occupational environment could expose workers to a wide variety of risk factors. Beside “classical” risk factors, such as chemical compounds, physical agents and biological agents, a group of "new” risk factors has become more and more prevalent over the last few decades; psychosocial hazards in occupational environments and exposure to nanoparticles are flawless examples of these potential issues for workers' health. This book aims to address principal “classical” risk factors by dealing extensively with occupational respiratory diseases, cardiovascular diseases related to work, occupational cancers, and occupational risks for hypersensitivity. Additionally, it attempts to shed light on a deepened treatise of occupational hazards related to the development of neurodegenerative diseases, psychosocial ailments, and ergonomic risk factors, which could result in cumulative trauma disorders of the upper limb. The second part of this book provides some advice regarding specific risk factors or specific occupational exposures: health issues related to exposure to mechanical vibrations, pesticides, nanomaterials, and in a hospital environment were used as examples to deepen the risk assessment and the analysis of health hazards. The authors hope to paint a global picture of the principal risk factors in occupational medicine. Given these premises, this book is not aimed to be comprehensive, but rather to provide an introductive and robust base for facing several current issues in occupational medicine.